GIS crash course (field data) ... - Kramer, Daniel (Zenodo, 2023)
This is a click-by-click crashcourse to get you from 0-GIS-knowledge to the minimum to work with field data. Originally, I developed this course for AGF-212 - Snow and Ice Processes for the University Centre in Svalbard. Thus, the topics are aimed towards the course content but the skills are transferable. And all data is freely available (yeahy!). The goal of the course is to be able to make a map during fieldwork to keep track of instruments and activities. Instructions 1) Download and unzip the file. 2) Click on GIS_crash_course 3) Open index.html The translation to French has been done by Annie Baneville, trad. a./C. Tr. ... : The course was developed for the University Centre in Svalbard. GRIMP has funded the translation to French. Data is available from the Norwegian Polar Institute data center. ...